Effect of aerosol fenoterol on the severity of bronchial hyperreactivity in patients with asthma. - Salome, C M (1983)
Beta adrenergic agents given by aerosol decrease the responsiveness of the airways to histamine and methacholine in subjects with asthma, causing a shift of the dose response curve to the right. To find out whether the shift is related to the dose of beta adrenergic agent given and to determine the duration of the reduced responsiveness, eight subjects with asthma were given histamine inhalation tests after inhaled saline and after increasing doses of inhaled fenoterol on different days. The histamine inhalation tests were repeated at hourly intervals for five hours after a selected dose of fenoterol. Fenoterol caused a dose related shift to the right of the histamine dose response curve in each subject and in some the dose response relationship reached the "non-symptomatic range." The shift in the dose response curve was short lived and had returned towards the control position within three hours in all subjects. There was no change in shape of the curves at the time of maximal shift. The results show that inhaled fenoterol greatly reduces the airway responsiveness to histamine, but up to 400 micrograms of fenoterol every four to five hours may be needed to keep the responsiveness of the airways in the non-symptomatic range.